2000
DOI: 10.1038/modpathol.3880195
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and In Situ Hybridization Analyses of Midkine Expression in Thyroid Papillary Carcinoma

Abstract: Midkine (MK) is a novel heparin-binding growth factor whose gene has been identified in embryonal carcinoma cells in early stages of retinoic acidinduced differentiation. We immunohistochemically examined 90 thyroid papillary carcinomas (85 invasive type and five encapsulated type), using a rat IgG2a monoclonal antibody against the carboxyl terminal region of human MK in archival paraffin sections. The thyroid tumors exhibited an intense reaction in the cytoplasm. Most of the papillary carcinomas (77/90), had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…Furthermore, overexpression of MK predicted a poor outcome in patients with invasive bladder cancer [53]. In thyroid papillary carcinomas the expression of MK has been shown to relate to the invasion of these carcinomas [54]. Two other studies have demonstrated an overexpression of MK in hepatocellular carcinomas and Sternberg Reed cells of Hodgkin's disease [55,56].…”
Section: Midkine and Pleiotropinmentioning
confidence: 99%
“…Furthermore, overexpression of MK predicted a poor outcome in patients with invasive bladder cancer [53]. In thyroid papillary carcinomas the expression of MK has been shown to relate to the invasion of these carcinomas [54]. Two other studies have demonstrated an overexpression of MK in hepatocellular carcinomas and Sternberg Reed cells of Hodgkin's disease [55,56].…”
Section: Midkine and Pleiotropinmentioning
confidence: 99%
“…Furthermore, overexpression of MK mRNA is positively correlated with advanced tumours and poor prognosis, especially in the case of patients with neuroblastoma and bladder carcinoma (Nakagawara et al, 1995;O'Brien et al, 1996). Immunohistochemical studies revealed MK protein expression in other carcinomas, including oral carcinoma (Ruan et al, 2007), oesophageal carcinoma (Ren and Zhang, 2006), gastrointestinal stromal tumours (Kaifi et al, 2007), liver carcinoma (Kato et al, 2000b), lung carcinoma (Sakitani et al, 1999), thyroid carcinoma (Kato et al, 2000a), and prostate carcinoma .…”
mentioning
confidence: 99%
“…Midkine (MK) is a novel heparin-binding growth factor found as a product of a retinoic acid-responsive gene (8). MK has been reported to be intensely expressed in various human tumors including lung (9), breast (10), gastric (11), colorectal (12), esophageal (13), liver (14), thyroid (15), prostate (16) and pancreatic (17). In addition, MK expression has been correlated with poor prognosis in patients with neuroblastomas (18), astrocytomas (19), pancreatic cancers (17) and gastrointestinal stromal tumors (20).…”
Section: Introductionmentioning
confidence: 99%